Cross-Border Acquisitions and Corporate Taxes: Efficiency and Tax Revenues - Pehr-Johan Norbäck; Lars Persson; Jonas Vlachos (Research Institute of Industrial Economics (IFN), 2006)
We find that reduced foreign corporate taxes may lead to inefficient foreign acquisitions if complementarities between foreign and domestic assets are low, and to efficient foreign acquisitions if such complementarities are high. Moreover, with large complementarities, foreign acquisitions can increase domestic tax revenues. The reason is that in the bidding competition between the foreign firms, all benefits from the acquisition, including tax advantages and evaded taxes, are competed away and captured by the domestic seller which, in turn, pays capital gains tax on the proceeds. Technical issues in the tax code, such as the treatment of goodwill deductibility, is also shown to crucially affect the pattern of foreign acquisitions.
Keywords: F23; 330; Tax Competition; Ownership; Tax Revenues; FDI; M&As; Direktinvestition; Übernahme; Steuerwettbewerb; Steuerwirkung; Steuereinnahmen; Theorie